Pengembangan Media Pembelajaran Berbasis Articulate Storyline dengan Pendekatan Etnomatematika untuk Meningkatkan Kemampuan Pemecahan Masalah Matematis Siswa SMP - Reny Kurniasari; Fitria Zana Kumala (Program Studi Pendidikan Matematika, 2025)
Students' mathematical problem-solving abilities are classified as very low, in part due to the lack of use of media variations linked to contextual materials. Based on these conditions, this study focused on developing digital learning media in Articulate Storyline using an ethnomathematics approach to ensure validity and effectiveness in improving eighth-grade students' mathematical problem-solving abilities in the topic of relations and functions. The research and development method applied is the ADDIE model, which includes the stages of Analysis, Design, Development, Implementation, and Evaluation. The sample of this study consisted of eighth-grade students at MTs Satu Atap Biroyatul Huda Cilongok, with the instruments used including interview guidelines, validation questionnaires, interestingness questionnaires, and tests. Media experts assessed this media as very valid based on validation results, with an average of 83.33% for the ethnomathematics material and context experts 83,5% and 95% for the mathematics teachers. The results of small-group trials showed that the percentage of interestingness reached 96.67%, and field trials reached 89.06% with a very interesting classification. The effectiveness test using N-Gain showed that the experimental class had an average N-Gain of 0.755 (high), while the control class had an average N-Gain of 0.3979 (moderate). The N-Gain effectiveness interpretation shows that the experimental class is classified as effective at 75.5%, while the control class is classified as ineffective at 39.79%. Therefore, digital learnin media based on Articulate Storyline, with an ethnomathematics approach, have validity and effectiveness in improving students' mathematical problem-solving abilities.